Pekanbaru Town Square Development With Concept Mix Use Building (Shopping Mall, Hotel, Condotel, Convention, Sport Centre) - Kurnain, Ahmad; Bambang Supeno; Muhammad Yazid; Rahmat Tisnawan; Rizki Ramadhan Husaini (Journal of Civil Engineering and Planning (JCEP), 2025)
This study assesses the financial feasibility of a privately financed infrastructure project under a Build-Operate-Transfer (BOT) scheme with a total investment of USD 76 million. The investment is distributed over a three-year construction phase, followed by a 30- to 60-year operation period generating annual net profits of USD 8.64 million. Key financial metrics including Net Present Value (NPV) and Internal Rate of Return (IRR) are utilized to evaluate the project. The results indicate a negative NPV of approximately USD -14.85 million for a 30-year operation, suggesting the project is not viable under a conservative time horizon. However, extending the operation to 60 years yields a positive NPV of USD +23.8 million and an estimated IRR of 11.7%, surpassing the assumed discount rate of 10%. These findings highlight the importance of operational duration in BOT projects and suggest that long-term operation is essential to achieve financial sustainability. Recommendations include extending the concession period and optimizing cost structures to enhance investment attractiveness.